Uji In-Vitro Daya Hambat Ekstrak Beberapa Jenis Tanaman terhadap Pertumbuhan Jamur Patogen Getah Kuning Buah Manggis - SUADA, I KETUT; SUNITI, NI WAYAN; SUNARIASIH, NI PUTU LINDA (Agrotrop : Journal on Agriculture Science; Vol 3 No 2 (2013))
In-vitro Testing of Inhibiting Ability of Some Plants Extractto the Growth of MangosteenYellow Latex Pathogens. The yellow latex disease decreases fruit quality of mangosteen because ofthe exogenic latex causing dirty the fruit, and the endogenic latex makes the bitter fruit taste, thereforethe fruit does not deserve to be consumed. The causal agent of the disease are fungus i.e.Verticilliumalbo-atrum, Fusarium oxysporum,andPestalotia macrotricha, therefore the research was aimedto find the plant extract that could act as antifungal agent. Screening on many kinds of plant extractthrough well difusion method were found that crude water extract of 10% concentration of kayusugih, kayu tulak, sereh dapur, beluntas, puring, sirih hutan, temen, and dapdap were only effectiveto suppress Verticillium albo-atrum.Methanolic plant extract of 10% of endongplant was only effectiveagainst Fusarium oxysporum, while the extract that effective against Pestalotia macrotricha wasnot found yet.
Keywords: yellow latex, plant extract, antifungal.